Fixed-dose, body weight-independent subcutaneous low molecular weight heparin Certoparin compared with adjusted-dose intravenous unfractionated heparin in patients with proximal deep venous thrombosis - Riess, Hanno; Koppenhagen, Klaus; Tolle, Alexander; Kemkes-Matthes, Bettina; Gräve, Michael; Patek, Frantisek; Drexler, Michael; Siemens, Hans-Joachim G.; Harenberg, Job; Weidinger, Gottfried; Brom, Joachim; Haas, Sylvia (Thrombosis and haemostasis, 2003)
Subcutaneous body weight-adjusted low molecular weight heparin (LMWH) has been proven as effective and safe as intravenous aPTT-adjusted unfractionated heparin (UFH) for the treatment of patients with acute deep venous thrombosis (DVT). In this study we evaluate the efficacy of the initial treatment of proximal DVT with a fixed-dose, body weight-independent application of the LMWH Certoparin with a six month follow-up. In a prospective, multicentre, randomized, active-controlled study 1220 patients with objectively diagnosed proximal DVT were randomly assigned to subcutaneous 8000 U anti-factor Xa of Certoparin twice daily for 10 to 14 days or intravenous aPTT-adjusted UFH for 5 to 8 days. Both regimen were followed by oral anticoagulation for 6 months. The primary end point was the rate of symptomatic and objectively confirmed thromboembolic events within 6 months. The aim of the study was to demonstrate the non-inferiority of the Certoparin regimen as compared to UFH. The per-protocol analysis revealed 22 (3.8%) thromboembolic events in the Certoparin group and 24 (4.3%) in patients assigned to UFH within 6 months, thereby proving the non-inferiority (p<0.01), confirmed by intent-to-treat analysis (p<0.001). Major bleeding occurred in 6 and 7 patients started on Certoparin or UFH during the treatment period. Thromboembolic events were equally distributed in body weight categories with < 50,50-80 and >80 kg as followed:0,3.6% and 4.1% of patients for the Certoparin group and 0, 4.6% and 4.2% of patients for the UFH group. The same was true for major bleeding complications with 0, 2.9% and 1.5% for Certoparin and 0, 3.5% and 4.2% for UFH. Overall mortality was 1.9 % in the Certoparin group and 2.7 % in the UFH group. Fixed-dose body weight-independent subcutaneous LMWH Certoparin is at least as efficacious and safe as intravenous aPTT-adjusted UFH for the initial treatment of acute proximal DVT. This effect is maintained during a 6-months follow-up of treatment with oral anticoagulation.